Perception of Environmental Education: Secondary Education Teacher Profiles and 2030 Agenda : Percepción de la educación ambiental: perfiles docentes de Educación Secundaria y Agenda 2030 para el Desarrollo Sostenible (Papeles, 2021)
Introduction: Can the social representations that teachers have on Environmental Education (EE) have an impact on achieving the Sustainable Development Goals (SDGs) of the 2030 Agenda?  To answer this question, the following objectives are proposed: study the evolution of the concept of Environmental Education, analyze the social representations of teachers on this subject and assess their impact on teaching practice due to their possible impact on the achievement of the objectives ODS. Methodology: For this reason, we have carried out an exploratory study of Secondary Education teachers in Valencia (Spain) using research techniques such as semi-structured interviews and pictorial representations. Results and discussion: The results show signs of correlation between environmental ideological positioning, social representations and the mixed social and environmental didactics. Conclusions: These results allow us to configure various teaching profiles of Environmental Education to address the 2030 Agenda in the educational field.
Keywords: perception; environmental education; Agenda 2030; teacher profiles; secondary education